The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1051/0004-6361:20066857
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of photospheric acoustic waves into non-magnetic solar atmosphere

Abstract: Aims. This paper aims to look at the propagation of synthetic photospheric oscillations from a point source into a two-dimensional non-magnetic solar atmosphere. It takes a particular interest in the leakage of 5-min global oscillations into the atmosphere, and aims to complement efforts on the driving of chromospheric dynamics (e.g. spicules and waves) by 5-min oscillations. Methods. A model solar atmosphere is constructed based on realistic temperature and gravitational stratification. The response of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 32 publications
(49 reference statements)
4
44
1
Order By: Relevance
“…The coincidence of the observed periods of coronal and photospheric oscillations logically leads to the idea that the photospheric oscillations leak into the corona along inclined magnetic fields (De Pontieu et al 2005;Erdélyi et al 2007;Fedun et al 2009). However, Murawski and Zaqarashvili (2010) and Zaqarashvili et al (2011) suggested that the observed periodicity in the solar corona is caused by quasi-periodic rebound shocks, originating from nonlinear wakes in the stratified atmosphere.…”
Section: Discussionmentioning
confidence: 95%
“…The coincidence of the observed periods of coronal and photospheric oscillations logically leads to the idea that the photospheric oscillations leak into the corona along inclined magnetic fields (De Pontieu et al 2005;Erdélyi et al 2007;Fedun et al 2009). However, Murawski and Zaqarashvili (2010) and Zaqarashvili et al (2011) suggested that the observed periodicity in the solar corona is caused by quasi-periodic rebound shocks, originating from nonlinear wakes in the stratified atmosphere.…”
Section: Discussionmentioning
confidence: 95%
“…We also want to point out that this model omits important physics, e.g. density stratification (Osterbrock 1961;Rosenthal et al 2002;Erdélyi et al 2007), but the idea is to use a very simple model to illustrate the possibility of photospheric seismology.…”
Section: Mathematical Frameworkmentioning
confidence: 99%
“…We showed that the field-free cavity regions under the magnetic canopy can trap high-frequency acoustic oscillations, leading to the observed increased high-frequency power in the photosphere, while the lower-frequency oscillations are channeled upwards in the form of magneto-acoustic waves (Erdélyi et al 2007;Srivastava et al 2008). However, those calculations have been performed without taking the gravitational stratification into account, which is important at the photospheric level.…”
Section: Introductionmentioning
confidence: 99%